The Effect of Cutting Speed of Nitrogen Laser Cutting on the Surface Texture of SUS 304 Plate - Pradana, Yanuar Rohmat Aji; Afrianto, Raka; Rahman, Chandra Hairat Abdul; Andoko, Andoko (Universitas Negeri Malang, 2023)
The focus of today’s machining industry is on how to maintain high productivity and low cost achieved by high tool life during the operation. Laser cutting is considered the right solution because it offers cutting speeds of up to 170000 mm/min through a non-contact process regardless of the workpiece material hardness. The aim of this study is to analyze the effect of cutting speed on the surface texture aspects namely surface roughness, kerf shape, and dross height on the stainless steel 304 plate after laser cutting. The nitrogen laser was utilized with the cutting speed of 400, 1700, and 2000 mm /min and the average roughness (Ra) was then measured using a surface roughness tester. On the other hand, the top, middle, and bottom area of the kerf surface as well as the dross height were analyzed by scanning electron microscopy (SEM). The highest Ra value was resulted at cutting speed of 2000 mm/min with 2.965 ± 0.05 μm while the lowest was at 1400 mm/min with 2.522 ± 0.16 μm. In parallel, the Ra was found to be higher when subjected gradually from the top to bottom zone. The kerf surface also proved that the top zone is dominated by the cutting zone, while the middle and bottom zone are characterized by the transition and deformation zone respectively. The width between kerf lines increased when the higher cutting speed was performed. Additionally, the larger dross height was found at the cutting speed of 1400 mm/min with 32.75 ± 5.21 μm and then degraded gradually at the higher cutting speed. The heat input and laser capability in exposing the material thickness are responsible for determining the corresponding surface texture aspects.